PENGARUH PENERAPAN PERMAINAN SCRABBLE UNTUK MENINGKATKAN KOSAKATA BAHASA INGGRIS SISWA KELAS VI SD DESA BANGUN REJO TANJUNG MORAWA - Zulkarnain Batubara,; Indra Agussamd,; Imran Surbakti, (Journal of Innovation Research and Knowledge, 2022)
This study was aimed to investigate the effect application of Scrabble board game in English learning of The Sixth elementary school students Bangun Rejo Village Tanjung Morawa District. Furthermore, it is also intended to analyze the increase of student vocabulary after using the Scrabble board game. By using quantitative methods, the data is presented in the form of concrete numbers and graphs. The results showed that: 1) The application of a Scrabble board game had a very good impact on English learning, indicated by 86% of student responses 2) There was a significant increase on student vocabulary after using Scrabble board game within two meetings, proved by N-Gain calculations which show the difference in improvement with the experimental class results were higher and the Paired Sample Test using SPSS version 25 showed Sig. 0,000 <0.05.